Optimizing an iron- and manganese-based electrocatalyst for the oxygen evolution reaction in a proton exchange membrane electrolyzer - Rosenthal, Moritz Karl; Moumaneix, Lilian; Rautama, Eeva Leena; Lahtinen, Jouko; Jiang, Hua; Cherevko, Serhiy; Priamushko, Tatiana; Kallio, Tanja (Chemical Engineering Journal, 2026)
The development of electrocatalysts based on earth-abundant elements has gained significant attention due to the scarcity and high cost of Ir- and Ru-based materials typically used in proton exchange membrane electrolyzers (PEMELs). This study focuses on Fe-Mn-based catalysts for promoting the oxygen evolution reaction (OER), the sluggish four-electron process at the anode of PEMELs, where acidic conditions and high anodic potentials (1.6–2.0 VRHE) often accelerate corrosion. The catalysts were synthesized via a hydrothermal method and optimized using a response surface design of experiments (DOE), followed by detailed physicochemical characterization. The optimized composition ( [Figure presented] ) demonstrates good electrochemical activity and stability, maintaining performance over 10,000 potential cycles between 1.2 and 2.0 VRHE, with a moderate shift in the overpotential required to reach 10 mAcm−2 (from 1.78 ViR−corr vs RHE to 1.84 ViR−corr vs RHE). Inductively coupled plasma mass spectrometry of flow cells scanning (SFC-ICP-MS) confirms high stability at elevated potentials, showing reduced [Figure presented] to [Figure presented] oxidation. At lower potentials (≤1.4VRHE), dissolution signals indicate reductive leaching of Fe and Mn. Integration of the catalyst into a laboratory PEMEL demonstrate operational stability, sustaining 10 mAcm−2 at 50 °C over 80 h, with a 50 mV increase in iR-corrected potential (1.82 to 1.87 V).
CRIS-Team Scopus Importer:2026-01-16
Keywords: Acidic oxygen evolution reaction; Design of experiments; Platinum group metal free; Proton exchange membrane electrolyzer; Scanning flow cell inductively coupled plasma mass spectrometry